2020
DOI: 10.1590/fst.12619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sonication and heat treatment on the physicochemical, nutritional and microbiological properties of different sugarcane variants

Abstract: Red sugarcane (RS) is a lesser bred of sugarcane variant in Malaysia compared to yellow sugarcane (YS), thus less data is available regarding this species. On this study, the physicochemical and microbiological properties of RS was determined and compared with YS under different conditions. Both sugarcane variants were subjected to heat and sonication treatments for 5 and 15 minutes as a method for preservation. RS contains a higher °Brix (15) compared to YS (14), and was unchanged while YS demonstrated a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Non-enzymatic browning occurs at high temperatures and causes the sucrose molecule to undergo inversion, this causes browning and affects the color of the beras kencur drink (Akbar & Murtini, 2018). Similar results have also been reported by Abid et al (2014); Jasmi et al (2020); Jabbar et al (2015), informing a significant difference in the TCD of the liquid sample after the thermosonic treatment.…”
Section: Colorsupporting
confidence: 78%
See 1 more Smart Citation
“…Non-enzymatic browning occurs at high temperatures and causes the sucrose molecule to undergo inversion, this causes browning and affects the color of the beras kencur drink (Akbar & Murtini, 2018). Similar results have also been reported by Abid et al (2014); Jasmi et al (2020); Jabbar et al (2015), informing a significant difference in the TCD of the liquid sample after the thermosonic treatment.…”
Section: Colorsupporting
confidence: 78%
“…showed the changes in the color value of beras kencur drink in various treatments. Abid et al (2014); Jasmi et al (2020); , exhibited significant differences in the colors of the thermosonic treated liquid samples.…”
Section: Colormentioning
confidence: 95%
“…Manzoor et al (2020) declared the maximum reductions for TMAB and YM counts as 1.95 log CFU/mL and 0.42 log CFU/mL after 40 min sonication treatment, respectively. Jasmi et al (2020) detected that all sonication treatments of sugarcane juice reduced the TMAB and YM counts to zero. The leading mechanism of sonication on microorganisms could be related to disruption of the microbial cells and modification of cellular activities (Hayer, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies have shown that slow pasteurization leads to reduced levels of some of the antioxidant components present in HM such as glutathione peroxidase (Silvestre et al, 2008), vitamin C (Moltó-Puigmartí et al, 2011, total antioxidant capacity (Nogueira et al, 2018;Silvestre et al, 2008) In this context, innovative methods of food preservation such as ultrasound (US), high pressure, ionizing radiation, pulsed electric field, microfiltration and ultraviolet radiation, have been tested as possible alternatives to conventional thermal treatments in order to maintain microbiological safety with less impact on nutritional, functional and sensory aspects (Monteiro et al, 2020;Shabbir et al, 2020;Jasmi et al, 2020;Awad et al, 2012). In this context, the treatment of food with ultrasound (US) can offer an alternative to traditional methods (Piñon et al, 2019;Fernández-Barbero et al, 2019).…”
Section: Impact Of Ultrasound Treatment On Viability Of Staphylococcumentioning
confidence: 99%